Benign Aspirates on Follow-Up FNA May Be Enough in Patients with Initial Atypia of Undetermined Significance/Follicular Lesion of Undetermined Significance. (13th February 2014) - Kim, Ga Ram; Yoon, Jung Hyun; Kim, Eun-Kyung; Moon, Hee Jung; Kwak, Jin Young
Abstract : Background. Management of thyroid nodules with benign aspirates following atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) is not well established. We reviewed the risk of malignancy and the role of ultrasound (US) features among thyroid nodules with benign results following initial AUS/FLUS diagnoses. Methods. From December 2009 to February 2011, a total of 114 nodules in 114 patients diagnosed as benign on follow-up fine-needle aspiration (FNA) after AUS/FLUS results were included in our study. Eight among 114 nodules were confirmed pathologically and 106 were clinically observed by a follow-up FNA or US. Suspicious US features were defined as markedly hypoechogenicity, irregular or microlobulated margin, presence of microcalcifications, and taller than wide shape. Results. There were 110 (96.5%) benign nodules and 4 (3.5%) malignant nodules. Two (4.8%) among 42 nodules without suspicious US features and 2 (2.8%) out of 72 nodules with suspicious US features were confirmed as malignancy, but there were no significant associations between the malignancy rate and US features (P = 0.625 ). Conclusion. Clinical follow-up instead of surgical excision or continuous repeat FNA may be enough for benign thyroid nodules after AUS/FLUS. The role of US features might be insignificant in the management of these nodules.